The role of agricultural cooperatives in mitigating opportunism in the context of complying with sustainability requirements: empirical evidence from Spain - Jorge Luis Sánchez-Navarro; Narciso Arcas-Lario; Jos Bijman; Miguel Hernández-Espallardo (Agricultural and Food Economics)
Abstract The convergence of emerging sustainability regulations and recommendations outlined in the European, national and regional agricultural policies, coupled with the growing demand from retailers for food produced through more sustainable agriculture practices, presents a substantial challenge for farmers. This challenge is further exacerbated by their limited access to essential information, knowledge, and resources necessary for compliance, which are often acquired through interactions with various stakeholders within the agri-food supply chain. Moreover, the inherent power asymmetry between small-scale farmers and their considerably larger counterparts, including input suppliers and agricultural product buyers, exposes farmers to opportunistic behaviours. In response to these challenges, agri-food cooperatives have been proposed as an organizational solution to mitigate opportunistic behaviour. However, empirical data-supported evidence of this proposition remains scarce. Drawing upon data obtained from Spanish farmers, our study investigates the impact of agri-food cooperatives on the incidence of opportunistic practices experienced by farmers during their interactions with suppliers and buyers. Through a propensity score matching analysis, our findings reveal that cooperative membership exerts a statistically significant negative influence on both supplier and buyer opportunism in the context of complying with sustainability requirements. These findings provide compelling empirical evidence of the pivotal role played by agri-food cooperatives in addressing opportunism within the supply chain. Importantly, they underscore the vital importance of cooperatives in mitigating the challenges associated with enhancing sustainability in agriculture.